High Morbidity and Mortality of Coronary Angiography without Further Intervention: the Lesson Learned from the Claimed Data, National Health Security Office, Thailand, Years 2016-2020 - คณานุรักษ์ ปานเทพ; เปี่ยมสมบูรณ์ ชุมพล; โฆษิตชัยวัฒน์ จิตติ; พรวิภาวี รัชนิศ; วีรกุล กัมปนาท (Journal of Health Science of Thailand, 2022)
Coronary angiography (CAG) remains the gold standard for diagnosis of coronary artery disease and is generally considered a safe procedure. Our recent evidences suggested CAG might have an unexpectedly high mortality and morbidity. We reviewed the clinical outcomes of total mortality and morbidity of CAG without further intervention (CAG only) from the claimed data base of total 100 private and government service units registered to the National Health Security Office (NHSO), 2016- 2020. It was found that, based on the 2016-2019 claimed data, there were 40,544 cases with CAG only, accounted for 40.9% of overall CAG. Among them, there were 1,320 in-hospital deaths (3.26%), with additional 698 deaths within 30 days after discharge, making total deaths of 2,018 cases (4.98%). Claimed data from 1 October 2019 - 30 September 2020 delineated the mean hospital mortality rate of 2.9% (0.11-50%). The average rate of stroke and acute kidney injury (AKI) was 1.25% (0.3-4.3%) and 7.5% (0.1-15%), respectively. These results were unexpectedly much higher than the international standard complication rate from CAG only procedure. Thus, it created further questions of appropriateness of indications, skill, decision and procedural safety. Owing to incomplete available data base and large amount of cases, it was almost impossible to clarify these results. To obtain more information, the NHSO Working Group decided to select three outcome parameters of CAG only including death, stroke, AKI. Second, an electronic data entry form (with excel conversion) detailing indication, diagnosis, result, complications and treatment was created to monitor service quality of both sides. Hopefully, we should be able to clarify those questions soon. At present, CAG only should be monitored as the high risk procedure until more data are available.